Sexual Risk Assessment Using Event History Calendars with Male and Female Adolescents - Martyn, Kristy K. (J Pediatr Health Care, 2012)
INTRODUCTION: The purpose of this study was to explore male and female adolescents’ perceptions of and differences in Event History Calendar (EHC) sexual risk assessment in a clinical setting. METHOD: This study is a secondary analysis exploring male and female qualitative data from a mixed methods study of adolescent and provider communication. Participants included 30 sexually active 15-19 year old male (N=11) and female (N=19) patients at a school-linked clinic. The adolescents completed a pre-clinic visit EHC and then discussed it with a nurse practitioner (NP) during their visit. The adolescents shared their perceptions of the EHCs in a post-clinic visit interview. RESULTS: Constant comparative analyses revealed gender differences in: 1) adolescents’ perceptions of how EHCs helped report, reflect on, and discuss sexual risk histories; 2) how adolescents self-administered EHCs; and 3) the histories they reported. DISCUSSION: The EHC was well received by both males and females resulting in more complete sexual risk history disclosure. Self-administration of the EHC is recommended for all adolescents, but further sexual risk assessment by NPs using EHCs is needed.